Pengaruh Media Wordwall Terhadap Minat Belajar Materi Peredaran Darah Siswa SD - Yunita, Fretika; Mustika, Dea (Cetta: Jurnal Ilmu Pendidikan, 2025)
This research aimed to analyze the influence of Wordwall media on the learning interest of fifth-grade students in the circulatory system topic at SDN 141 Pekanbaru. A quasi-experimental quantitative approach was employed, with the entire fifth-grade student population (67 students) serving as the study population. Samples were selected using purposive sampling, with Class V A (36 students) designated as the experimental group utilizing Wordwall, and Class V B (31 students) as the control group receiving conventional learning.Learning interest data was collected using a validated and reliable 4-point Likert scale questionnaire. The data was then analyzed using SPSS 24, involving normality tests (Shapiro-Wilk) and homogeneity tests (Levene's Test), followed by a Paired Samples T-Test. The research findings indicate that Wordwall significantly increased students' learning interest, with the experimental group showing an average difference of 31.83 points, significantly higher than the control group's 13.21 points. The implication of this study is that interactive media such as Wordwall are effective in addressing low learning interest in abstract topics. Therefore, Wordwall is recommended as an innovation for science learning in elementary schools to enhance student appeal, participation, motivation, and comprehension.